2008
DOI: 10.1002/da.20371
|View full text |Cite
|
Sign up to set email alerts
|

Beck Depression Inventory II: evaluation of the psychometric properties and cut-off points in a Turkish adult population

Abstract: Numerous studies have been previously conducted to assess the Beck Depression Inventory-II's [BDI II; Beck et al., 1996] psychometric properties. However, none of these studies has examined whether the original cut-off scores were applicable to other cultures. Thus, in addition to evaluating its psychometric properties, we also determined the cut-off scores of the BDI II for the Turkish population. Data from nonclinical (n = 362) and clinical psychiatric outpatients diagnosed as depressive disorder according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(105 citation statements)
references
References 23 publications
2
97
0
6
Order By: Relevance
“…[12] A BDI score of 21 has been suggested as a cut-off value for the diagnosis of depression in a Korean population. [14] The validation and reliability study in a Turkish population was made by Kapci et al, [15] and a BDI score of 17 or greater was a cut-off value for diagnosis of depression.…”
Section: Quality Of Lifementioning
confidence: 99%
“…[12] A BDI score of 21 has been suggested as a cut-off value for the diagnosis of depression in a Korean population. [14] The validation and reliability study in a Turkish population was made by Kapci et al, [15] and a BDI score of 17 or greater was a cut-off value for diagnosis of depression.…”
Section: Quality Of Lifementioning
confidence: 99%
“…However, according to many studies this demonstrable cognitive dysfunction in patients with FM cannot be attributed solely to co-occurring psychiatric disorders such as depression, and that it is related with pain, fatigue and many to the impact that pain has on a patient [24]. According to study evaluating the psychometric properties and cut-off points of Beck Depression Inventory Scale for Turkish population, authors have determined the cut-off scores for the Turkish population revealing 0-12 for minimal, 13-18 for mild, 19-28 for moderate and 29-63 for severe depression [17]. And in our study we have found that in both groups total scores of BDI revealed mild depression.…”
Section: Discussionmentioning
confidence: 99%
“…A lower total score indicates less effect of fatigue on everyday life [16]. Depressive symptoms in all of the groups were obtained from the Beck Depression Inventory (BDI) [17]. It consists of 21 groups of items that assess both cognitive/affective and vegetative signs of depression.…”
Section: Methodsmentioning
confidence: 99%
“…Dressing and self care, raising, eating, walking, hygiene, reach, grip and activities were evaluated. Information about the psychological status was assessed with Beck Depression Inventory (BDI) (8).…”
Section: Methodsmentioning
confidence: 99%